تأثير تطبيقات الذكاء الاصطناعي على جودة التعليم العالي دراسة ميدانية بجامعة جيجل - بوشلاغم، حنان (جامعة الوادي University of Eloued, 2025)
This study aims to determine the impact of artificial intelligence applications on the quality of higher education at the University of Jijel. To achieve this, a set of hypotheses were formulated and tested using a set of statistical methods based on the SPSS program. was used, where the partial least squares path analysis method was adopted using the PLSPM software package to analyze the data and test the hypotheses. The population of the current study consists of all permanent professors, numbering 1282. A cross-sectional sample was used. The research sample was estimated at 105 people. The questionnaire was used as the basic tool for data collection. After translating and analyzing the data, the study concluded that artificial intelligence applications have a positive impact on the quality of higher education and that by carefully examining the results and recommendations presented here, educational institutions can benefit from the power of artificial intelligence to create more effective training. and quality education.
The impact of artificial intelligence applications on the quality of higher education A field study atJijel University
Keywords: الذكاء; الصناعة; الذكاء الاصطناعي; التعليم العالي; الجامعة; intelligence; industry; artificial intelligence; highereducation; university